1992
DOI: 10.1002/bjs.1800790840
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 5-fluorouracil and folinic acid on colonic healing: An experimental study in the rat

Abstract: Male Wistar rats were subjected to colonic resection and randomized to one of four groups: control group (intraperitoneal NaCl, intravenous NaCl); 5-fluorouracil (5-FU) group (intraperitoneal 5-FU, intravenous NaCl); folinic acid group (intraperitoneal NaCl, intravenous folinic acid); and 5-FU-folinic acid group (intraperitoneal 5-FU, intravenous folinic acid). Treatment was started immediately after surgery and continued until the animals were killed at 3 or 7 days. Anastomotic complications (abscesses or deh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
43
2
8

Year Published

1994
1994
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 13 publications
8
43
2
8
Order By: Relevance
“…On the 7th PO day, bursting pressure values in the IV 5-FU group were significantly lower than the IP group. Similar results have been found in previously reported studies [22,32,33] . Graf et al [32] reported that early postoperative 5-FU administration had a negative impact on the bursting strength of colonic anastomosis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…On the 7th PO day, bursting pressure values in the IV 5-FU group were significantly lower than the IP group. Similar results have been found in previously reported studies [22,32,33] . Graf et al [32] reported that early postoperative 5-FU administration had a negative impact on the bursting strength of colonic anastomosis.…”
Section: Discussionsupporting
confidence: 93%
“…All rats lost weight compared with baseline values during 5-FU administration and after the operation, which was statistically significant in the IV group. These results were concordant with reports from the literature [6,8,32] . Weight loss after 5-FU is related to anastomotic healing.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, an experimental study showed an impaired healing after i.p. 5-FU, but when folinic acid was added, no further deterioration occurred (Graf et al, 1992). However, this problem and other chemotherapy-related toxicities have been investigated in several clinical studies and this form of administration has not been associated with an increased complication rate (Graf et al, 1994c;Vaillant et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies using immediate post-operative intraperitoneal 5-FU are in progress Graf et al, 1994 (Martens et al, 1992a). Daily intraperitoneal administration of 5-FU alone from the day of surgery onwards until sacrifice after 7 days strongly inhibits anastomotic repair in the rat intestine (Graf et al, 1992;de Waard et al, 1995 were killed 3 and 7 days after operation. Collagen synthesis was measured in three groups of animals (n = 6): a control group, a 5-FU group and a group which received 5-FU plus levamisole.…”
mentioning
confidence: 99%